The Dung Beetle Oxyomus of Taiwan (Coleoptera: Scarabaeidae): Review of the Fauna, a New Species and its Larva Associated by DNA Barcoding - Ho, Bin-Hong; Hu, Fang-Shuo; Fikáček, Martin (Zoological studies, 2022)
The Taiwanese fauna of the dung beetle genus Oxyomus Dejean, 1833 (Coleoptera: Scarabaeidae: Aphodiinae) is reviewed based on museum specimens and newly collected material. Four species, all endemic to Taiwan, are recognized, one of which is newly described here: O. alligator sp. nov. Remaining species are diagnosed, compared with similar relatives from outside of Taiwan, and their distribution is mapped. We show that Taiwanese Oxyomus species form three distinct morphological groups, similar to species from Japan, SE Asia and Malay Archipelago, respectively, indicating a possible composite origin of Taiwanese fauna. The species occur in submontane and montane forests at altitudes of 700-2550 m including the secondary Cryptomeria ones. Available data confirm their association with dung of various forest mammals (monkeys, muntjacs and serows), although the discovery of larvae in sifted forest leaf litter may indicate they can also develop in nutrient-rich substrate around the dung. The larva of O. alligator sp. nov. is described in detail, based on the larval specimens associated with adults by DNA barcodes. Larvae of Oxyomus alligator sp. nov. are similar to those of the European O. sylvestris (Scopoli, 1763), with important differences only found on maxilla and abdominal apex.
Keywords: Aphodiinae; Dung beetles; Taiwan; Immature stages; New species; Distribution; DNA barcoding; Oxyomus; Endemism